Regulatory compliance in the Kenyan dairy sector: Awareness and compliance among farmers and vendors - Brown, Lahra Harcourt; Alonso, Silvia; Lindahl, Johanna; Varnell, Hannah; Hoffmann, Vivian; Grace, Delia (International Food Policy Research Institute, 2019)
The purpose of this research note is to describe relevant policies and standards, and to summarise recent research and literature to gain insight into compliance with dairy standards in Kenya. We highlight key points of the main policies pertaining to the sale of dairy products, and present unpublished findings from three recent studies conducted by the International Livestock Research Institute (ILRI) and partners and the results of a rapid literature review.